Enhancing Financial Risk Management in the Digital Age: A Systematic Review - Annisa Rahma Dianti (Arthatama: Journal of Business Management and Accounting, 2023)
The rapid advancement of digital technologies has transformed financial risk management, introducing both opportunities and challenges. This study systematically reviews the impact of big data analytics, artificial intelligence (AI), blockchain, and cloud computing on risk mitigation strategies. Using the Systematic Literature Review (SLR) method, recent scholarly contributions are analyzed to evaluate how digital innovations enhance predictive risk detection, transaction transparency, and operational flexibility. Findings indicate that AI and big data significantly improve risk prediction accuracy, blockchain enhances security and trust in financial transactions, and cloud computing facilitates scalable data management. However, regulatory uncertainty, cybersecurity vulnerabilities, and organizational resistance remain major challenges to widespread adoption. This study emphasizes the necessity of adaptive regulations, stronger cybersecurity frameworks, and cross-sector collaboration to optimize the benefits of digital transformation in financial risk management. The results provide valuable insights for policymakers, financial institutions, and researchers in developing more resilient and technology-driven risk mitigation strategies.